UMP ranked 201 250 best in THE Asia ranking - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 23 June 2023 - Universiti Malaysia Pahang (UMP) continues to excel when ranked 201-250 in the Times Higher Education Asia University Rankings 2023 (THE Asia) for the first time this year.